Leaching of gold ores with oxidizing salts in acidic medium through the severe process - Palacios Calizaya, Severo (2002)
The work of leaching is developed in Fewer, Concentrated and Refractory Material (sulfured), in pulp or particles (agitation or piles) to ambient temperature in advance of maximum leaching of twelve hours, using like half lixiviante the acid sulfuric concentrate added salts oxidizers like the chlorides and nitrate of sodium or ammonium nitrate in different proportions. The results obtained regarding the recovery of gold reach 98%. If the gold is encapsulated in the quartz or auriferous sand, fluoride of sodium will be added (never to use the calcium, because it forms plaster that hinders the process) with the purpose of dissolving the quartz, it doesn’t dissolve neither complex form with the gold, it is also good to leave in you liberate noble metals as the titanium, platinum, talio, germanium, etc., those which then are recovered with the means lixiviante to which I have denominated SEVERO Process.